BUSINESS GOODWILL AND REPUTATION – WITH SPECIFIC REFERENCE TO INTELLECTUAL PROPERTY LAW - Hidhu, Lisha (PEOPLE: International Journal of Social Sciences, 2019)
Passing off protects customer’s goodwill, that is, traders spend a great deal of effort and expense in building an identifiable reputation in order to create and enhance a market for their goods and services. There can be no goodwill without a reputation, though a reputation may exist without goodwill.Trademarks help to maintain commercial reputation. An equally significant protection is afforded through the specific law. Since 1896, there has been consistent development of this form of tort, but there is no judicial consensus as to the legitimate extent of protection required. The alternative suggestion of malicious, falsehood also failed to assume the significance it demanded. Unlike other forms of intellectual property, registered trademarks and passing off, focus on the producer’s reputation and goodwill.